Practical Optimum Design Method of Axial-Flux-type PM Motors using 2D Linear Model - Yaginuma, K.; Kimura, Y.; Hara, T.; Ueda, Y.; Nakamura, K. (Transaction of the Magnetics Society of Japan Special Issues, 2025)
Since axial-flux-type motors do not have a uniform structure in the axial direction, three-dimensional (3D) electromagnetic field analysis is required, which increases the calculation time remarkably when seeking optimum shapes and dimensions using optimum design algorithms, such as the genetic algorithm (GA). This paper presents a practical optimum design method using a two-dimensional (2D) linear model of axial-flux-type PM motors. It is demonstrated that the calculation accuracy for torque, losses, and efficiency using the proposed 2D linear model is almost equivalent to that of conventional 3D models, while significantly reducing the calculation time required for optimization.